Molecularly Imprinted Materials for Selective Biological Recognition. Issue 17 (21st May 2019) - Zhang, Nan; Zhang, Nan; Xu, Yarong; Li, Zhiling; Yan, Chaoren; Mei, Kun; Ding, Minling; Ding, Shichao; Guan, Ping; Qian, Liwei; Du, Chunbao; Hu, Xiaoling
Abstract: Molecular imprinting is an approach of generating imprinting cavities in polymer structures that are compatible with the target molecules. The cavities have memory for shape and chemical recognition, similar to the recognition mechanism of antigen–antibody in organisms. Their structures are also called biomimetic receptors or synthetic receptors. Owing to the excellent selectivity and unique structural predictability of molecularly imprinted materials (MIMs), practical MIMs have become a rapidly evolving research area providing key factors for understanding separation, recognition, and regenerative properties toward biological small molecules to biomacromolecules, even cell and microorganism. In this review, the characteristics, morphologies, and applicability of currently popular carrier materials for molecular imprinting, especially the fundamental role of hydrogels, porous materials, hierarchical nanoparticles, and 2D materials in the separation and recognition of biological templates are discussed. Moreover, through a series of case studies, emphasis is given on introducing imprinting strategies for biological templates with different molecular scales. In particular, the differences and connections between small molecular imprinting (bulk imprinting, "dummy" template imprinting, etc.), large molecular imprinting (surface imprinting, interfacial imprinting, etc.), and cell imprinting strategies are demonstrated in detail. Finally, future research directions are provided. Abstract : The characteristics, structure, and applicability of currently popular carrier materials for molecular imprinting on the recognition of biological templates are introduced. The differences and connections between various imprinting strategies toward biological templates with different molecular scales are summarized in detail.